Study of the Oscillations of a Composite Carding Drum with Toothed and Needle-Type Garnitures - Mirzaev Otabek Abdukarimovich (EDUMALSYS Journal of Research in Education Management, 2026)
This article theoretically examines the oscillatory behavior of a composite carding drum positioned in the discretization zone of pneumatic–mechanical spinning machines in order to improve technological efficiency. The study aims to analyze the motion characteristics of the drum and determine how the oscillations of its toothed and needle-type garnitures depend on key structural and operating parameters. Using a theoretical approach, the laws of motion and their solutions were derived through Lagrange’s equations of the second kind. The analysis demonstrates the parametric dependence of oscillatory responses in the existing carding drum system, particularly with respect to the toothed and needle-type garnitures, and presents the resulting regularities in graphical form. These findings provide a scientific explanation of the mechanical behavior of the drum within the discretization zone and contribute to a more rigorous understanding of oscillation dynamics in pneumatic–mechanical spinning technology. The study offers a theoretical basis for technological improvement by informing the optimization of carding drum design and operating conditions to enhance system performance and efficiency.